Kajian Efek Stimulansia Beberapa Minuman Energi Kemasan Botol Yang Beredar Di Pasaran - Helmi Arifin; Benny Benny; Elisma Elisma (Jurnal Farmasi Higea, 2012)
A research on the activity of the central nervous system stimulant of some bottled energy drinks on the market for white mice (Mus musculus, L.) has been done. The samples labelled Minuman Energi (ME) 1, ME 2, ME 3, ME 4 and ME 5 and administered perorally. Each sample has administration volume of 0.4 mL/20g BW. Comparator used is caffeine (6.5 mg/Kg BW). Parameters used for stimulant activity were endurance tested using Rotary road, while  motoric activity and curiosity tested using Automatic Hole Board. From the research that has been done, it is known that ME 1, ME 2, ME 3, ME 4 and ME 5 has a central nervous system stimulant activity by increasing endurance, motoric activity and curiosity in mice significantly.